Investigating the Antimicrobial Properties of Garlic and Onion Against Gram Positive and Negative Bacteria, E. coli and S. aureus - Mohd Noor, Siti Fatimah; Abdul Nadir Nurijil, Nor Nadria; Yuszaarul, Nurul Athirah; Yang Oriyana Mazri, Yang Nurin Qistina; Abdul Halim, Norhazimah (Multidisciplinary Applied Research and Innovation, 2025)
The present investigation examines the antimicrobial potency of garlic and onion against both Gram-positive and Gram-negative bacteria, with a focus on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The objective is to assess the viability of these natural substances as potential antibacterial alternatives amidst the escalating challenge of antibiotic resistance. Garlic, abundant in organosulfur compounds such as allicin, ajoene, and allyl sulphides, is well-documented for its bactericidal effects. Onion, which contains quercetin and sulphur compounds, also exhibits antimicrobial The study aims to determines the susceptibility of the chosen antimicrobial ingredients and the minimum inhibitory concentrations (MICs) of extracts from garlic and onion when applied to both bacterial species. Findings reveal that garlic demonstrates considerable antibacterial activity against S. aureus, achieving a lower MIC than that observed for E. coli. While the antimicrobial efficacy of onion is unresolved, showing result with no significant findings against inhibiting both bacteria. The research posits that only garlic is integral to the formulation of novel antibacterial agents.